Vertical effective stress as a control on quartz cementation in sandstones. (December 2018) - Oye, Olakunle J.; Aplin, Andrew C.; Jones, Stuart J.; Gluyas, Jon G.; Bowen, Leon; Orland, Ian J.; Valley, John W.
Abstract: Temperature-controlled precipitation kinetics has become the overwhelmingly dominant hypothesis for the control of quartz cementation in sandstones. Here, we integrate quantitative petrographic data, high spatial resolution oxygen isotope analyses of quartz cement, basin modelling and a kinetic model for quartz precipitation to suggest that the supply of silica from stress-sensitive intergranular pressure dissolution at grain contacts is in fact a key control on quartz cementation in sandstones. We present data from highly overpressured sandstones in which, despite the current burial temperature of 190 °C, quartz cement occurs in low amounts (4.6 ± 1.2% of bulk volume). In situ oxygen isotope data across quartz overgrowths suggest that cementation occurred over 100 Ma and a temperature range of 80–150 °C, during which time high fluid overpressures resulted in consistently low vertical effective stress. We argue that the very low amounts of quartz cement can only be explained by the low vertical effective stress which occurred throughout the burial history and which restricted silica supply as a result of a low rate of intergranular pressure dissolution at grain contacts. Highlights: Very low volumes of quartz cement in sandstones buried to 190 °C Temperature-controlled precipitation kinetic model cannot explain the lack of quartz cement Oxygen isotope data support very low rates of quartz cementation History of low effective stress restricts silica supply via dissolution at grain contacts